Abraham Lincoln as a man of ideas - Guelzo, Allen C. (Southern Illinois University Press, 2009)
"Despite the most meager of formal educations, Lincoln had a tremendous intellectual curiosity that drove him into the circle of Enlightenment philosophy and democratic political ideology. And from these, Lincoln developed a set of political convictions that guided him throughout his life and his presidency. This compilation of ten essays from Lincoln scholar Allen C. Guelzo uncovers the hidden sources of Lincoln's ideas and examines the beliefs that directed his career and brought an end to slavery and the Civil War."--Google books viewed Feb. 4, 2021